(untitled) (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Globally, livestock diseases are major constraints to animal production and management, usually resulting in economic losses, reduced productivity and quality of livestock products. The livestock diseases prevalent in south east Nigeria were evaluated based on data collected between January 2010- June 2023 from the epidemiology unit of the Federal Department of Veterinary and Pest control services, Federal Ministry of Agriculture and Rural Development Abuja, Nigeria. Diseases of cattle reported ranging from the highest to the least occurrence included, Contagious Bovine Pleuropneumonia (CBPP), Bovine Tuberculosis, Brucellosis, Fascioliasis and Mastitis. Major disease of small ruminants (sheep and goats) was Pests des Petits ruminants (PPR). Diseases of pigs reported included: African swine fever, Swine Erysipelas and piglet anaemia. Poultry diseases were New Castle Disease (NCD), Infectious Bursal Disease (IBD), Coccidiosis, Fowl typhoid, Fowl pox and Highly Pathogenic Avian influenza (HPAI). The article also reviewed the notifiable diseases reported by Nigeria Center for Disease Control through its Integrated Disease Surveillance and Response system (IDSR) known to be zoonotic. Diseases in this category were Tuberculosis, Anthrax, Rabies, HPAI, Food and water borne diseases such as Brucellosis, Colibacillosis, Cysticercosis. Control programmes included; Biosecurity measures, disease surveillance in flocks and farms, seromonitoring of animals, routine vaccination, accurate diagnosis and treatment of sick animals, stamping out flocks once disease is detected as in the control of HPAI and CBPP. The evaluation of the disease prevalence, economic and public health effects of these diseases could not be accomplished in the course of this review as a result of underreporting and inaccurate disease identification due to lack of basic veterinary diagnostic facilities. It was therefore recommended that developing an operational digital livestock information system for livestock farmers, disease surveillance and reporting will be needful. Decentralizing the National Veterinary Research Institute Vom function of disease diagnosis/surveillance to the six geopolitical regions in Nigeria as well as employing the one health approach to livestock disease control and management would also be apposite in unlocking the livestock potentials of Southeast Nigeria.